Aproximações entre o método fenomenológico de Edmund Husserl e o método ontopsicológico de Antonio Meneghetti na Psicologia - Gazzaneo, Luiz Victor Azevedo (2024)
This research proposes, from a theoretical perspective, approaches between Edmund Husserl's phenomenological method and Antonio Meneghetti's ontopsychological method, especially in Psychology. As the research problem, it started with the following question: “can the method elaborated by Ontopsychology constitute a psychological-practical passage of Edmund Husserl's proposal for a phenomenological Psychology?”. Through bibliographical research, the beginning of the work consisted of an exposition of introductory aspects of Phenomenology, its main ideas and criticisms and the understanding of its method proposal, especially for Psychology. In a second moment, the Ontopsychology, its theoretical bases, scientific novelties and method were addressed. Subsequently, dialogues between the two sciences were explored, in the aspectos of concepts, methods and purposes. This approach proposal was made based on the analysis of conceptual pairs that presented affinity – in conception, function or scope within the respective scientific projects – and culminated in the analysis of “evidence” and the “ontological nexus” as central elements to think about the relation between the two sciences. These two concepts highlight more clearly the viability of Ontopsychology as one of the possible forms of a Phenomenological Psychology. From the research, it was possible to visualize the correspondences and interactions between the key concepts of both approaches, highlighting the similarities and complementarities between them. In this way, the analysis of the evidence and the ontological nexus revealed the coherence and theoretical-methodical affinity between Ontopsychology and Husserl's phenomenological Psychology, providing support for considering the first as a contemporary manifestation of the second. Finally, the result verified from the research carried out is that Ontopsychology, through its theory and method, can constitute the theoretical-methodical concretization of a Phenomenological Psychology. This finding was achieved through comparative analysis between the principles, concepts and methods of the two disciplines, which revealed significant coherence and complementarity. Consequently, it became clear that the approach proposed by Ontopsychology has great potential to incorporate and expand the foundations of Husserl's Phenomenological Psychology, representing a contemporary continuation of this theoretical framework.